Passiflora actinia HOOKER VEGETATIVE PROPAGATION BY MICROPROPAGATION AND MIDDLE BRUNCHING CUTTING - KOCH, Regina Canestraro (Scientia Agraria, 2000)
This work was made to study the propagation of Passiflora actinia Hooker, an edible and native fruit species of Paraná state, seeking its preservation and valuing its biodiversity economically. For the in vitro experiments mature fruits were collected, of the which were extracted the seeds and stored in flasks closed under refrigeration. As explants source was used plantlets obtained startinq from seeds germinated in vitro. The asepsis of the seeds was accomplished by the immersion in ethanol 10% for 1 minute proceeded by the immersion in solution of hipoclorite of sodium 2,5% for 30 minutes. The plantlets with 4 to 5 leaves was segmented and placed in the basic middle of culture (MS), added with BAP (1 mgL-1), AIB (0,01 mg.L-1) or both regulators. The delineation was made completely randomized with 36 repetitions and 3 to 4 explants for flask, being considered each flask as a portion. The material was evaluated until the second transplant. In the basic middle added with BAP happened intense multiplication of the used segments, being normal the tufts formation, and eventual formation of rootses in the base middle added with AIB happened the formation of rootses in the base of the branchings and the lengthening of the plantlets that presented, great development aspect. In the basic middle added with BAP and AIB happened the multiplication of almost all the segments, but with smaller proportion than the cultivated in the basic middle added with AIB. ln this middle the branchings happened in tufts form with little formation of rootses. In the semihardwood cuttings two experiments were driven to verify the effect of different concentrations of AIB and of ethanol. ln the experiment with AIB the following concentrations were tested: 0, 250, 500 and 1000 mg.-1. In the experiment with ethanol the treatments were: testimony, water, ethanol 10%, 30%, 50% and 70%. All the treatments were applied for immersion of the base of the cuttings (2 em) for 1 minute. In both experiments the delineation was made in randon blocks with 5 repetitions and 20 cuttings for portion. The evaluation was made seven weeks after the installation. Significant differences were not observed among the treatments, in both experiments, for whole the analyzed variables, except for the number of rootses emitted by cutting for the concentrations of AIB, that 1 presented a significant lineal regression. The rooting percentage was elevated, being on the average 90% in the experiment with AIB and 70% in the experiment with ethanol. Therefore, the Passiflora actinia can be spread by means 6 semihardwood cuttings without the use of growth regulators. Therefore, it is ended that these forms of propagation of Passiflora actinia are viable for the production clonal of dumb.